2009
DOI: 10.1016/j.immuni.2009.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Deltex1 Is a Target of the Transcription Factor NFAT that Promotes T Cell Anergy

Abstract: The molecular process underlying T cell anergy is incompletely understood. Deltex1 (DTX1) is a Notch target with unknown physiological function. Here we show that Dtx1 was a transcription target of nuclear factor of activated T cells (NFAT) and participated in T cell anergy. DTX1 protein was upregulated during T cell anergy, and transgenic expression of Dtx1 attenuated T cell activation. DTX1 inhibited T cell activation by both E3-dependent and E3-independent mechanisms. In addition, DTX1 suppressed T cell act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 42 publications
4
51
0
Order By: Relevance
“…Knockout of DTX1 eliminates restriction in T cell activation, confers resistance to anergy induction, and results in generation of autoimmune syndromes in mice (23). DTX1 promotes the degradation of MEK kinase 1 and stimulates the expression of Cbl-b and GADD45b (23). In the current study, we found that DTX1 also targets PKCu for degradation.…”
supporting
confidence: 56%
See 4 more Smart Citations
“…Knockout of DTX1 eliminates restriction in T cell activation, confers resistance to anergy induction, and results in generation of autoimmune syndromes in mice (23). DTX1 promotes the degradation of MEK kinase 1 and stimulates the expression of Cbl-b and GADD45b (23). In the current study, we found that DTX1 also targets PKCu for degradation.…”
supporting
confidence: 56%
“…We have previously demonstrated that DTX1 promotes the expression of Cblb mRNA (23). In Jurkat cells treated with A23187, knockdown of DTX1 impaired the induction of Cbl-b (Fig.…”
Section: Dtx1 Interacts With Cbl-b and Increases The Stability Of Cblmentioning
confidence: 77%
See 3 more Smart Citations